Concrete cities : why we need to build differently / Rob Imrie. - Imrie, Robert, 1958- (Bristol University Press, 2021)
Global building and construction cultures are hard-wired to constructing too much, too badly, with major social and ecological consequences. Rob Imrie calls us to build less and to build better as a pre-requisite for enhancing welfare and well-being.